2013
DOI: 10.1007/978-3-642-38844-6_25
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Domain Collaborative Recommendation in a Cold-Start Context: The Impact of User Profile Size on the Quality of Recommendation

Abstract: Abstract. Most of the research studies on recommender systems are focused on single-domain recommendations. With the growth of multidomain internet stores such as iTunes, Google Play, and Amazon.com, an opportunity to offer recommendations across different domains become more and more attractive. But there are few research studies on cross-domain recommender systems. In this paper, we study both the cold-start problem and the hypothesis that cross-domain recommendations provide more accuracy using a large volu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 7 publications
0
28
0
Order By: Relevance
“…There are different approaches for addressing cross domain recommendation. One approach is to assume that different domains share similar set of users but not the items, as illustrated in [20]. In their work, the authors augmented data from rating of movies and books from datasets that have common users.…”
Section: Related Workmentioning
confidence: 99%
“…There are different approaches for addressing cross domain recommendation. One approach is to assume that different domains share similar set of users but not the items, as illustrated in [20]. In their work, the authors augmented data from rating of movies and books from datasets that have common users.…”
Section: Related Workmentioning
confidence: 99%
“…Another study with positive results was conducted by Abel et al The dataset contained information related to the same users from 7 different OSNs [1]. Sahebi and Brusilovsky demonstrated the usefulness of recommendations based on source domains to overcome cold start problem [18].…”
Section: Cross-domain Recommendationsmentioning
confidence: 99%
“…Another study with positive results was conducted by Abel et al The dataset contained information related to the same users from 7 different OSNs (Abel et al, 2013). Sahebi et al demonstrated the usefulness of recommendations based on additional domains to overcome cold start problem (Sahebi and Brusilovsky, 2013). Most works on cross-domain recommender systems focus on the situation when users or both users and items of several domains overlap (Cantador and Cremonesi, 2014).…”
Section: Related Workmentioning
confidence: 99%